2016
DOI: 10.1111/jvec.12201
|View full text |Cite
|
Sign up to set email alerts
|

Infestation and seasonal activity of Ixodes vespertilionis Koch, 1844 (Acari: Ixodidae) on the Maghreb mouse-eared bat, Myotis punicus Felten, 1977, in northeastern Algeria

Abstract: Infestation of Ixodes vespertilionis Koch, 1844 on Myotis punicus Felten, 1977 from two sites (Trios Tunnel and Sidi Trad cave) in northeastern Algeria was studied. An overall infestation of 41.4% for all stages was found among bats collected from both sites. By stage, a total of eight females, 70 nymphs, and 107 larvae were recovered from both populations. The number of females recovered per bat at Sidi Trad ranged from 0‐1, for nymphs 0‐2, and for larvae 0‐2. While no female ticks were collected at Trios Tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In Scandinavia and the Baltic States, the tick is completely absent (Hornok 2017). Other reports include Algeria, Turkey, Iran, Russia and China, with a wide variety of bat species as hosts for both immature and adult stages (Bendjeddou et al 2016). In Germany, it is relatively seldom found because its main hosts, horseshoe bats (Rhinolophus spp.…”
Section: Ixodes (Eschatocephalus) Vespertilionis Kochmentioning
confidence: 99%
“…In Scandinavia and the Baltic States, the tick is completely absent (Hornok 2017). Other reports include Algeria, Turkey, Iran, Russia and China, with a wide variety of bat species as hosts for both immature and adult stages (Bendjeddou et al 2016). In Germany, it is relatively seldom found because its main hosts, horseshoe bats (Rhinolophus spp.…”
Section: Ixodes (Eschatocephalus) Vespertilionis Kochmentioning
confidence: 99%
“…Remarks: This tick was found on three bat hosts collected from eight sites. Bendjeddou et al () studied the infestation of Ixodes vespertilionis on M. punicus from two sites in northeastern Algeria. Arthur () and Kolonin () gave details on bat species hosting I. vespertilionis worldwide; including Hipposideros caffer, M. schreibersi, Myotis daubentoni, M. myotis, Rh.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first comprehensive study of the ectoparasites of bats in Algeria. Previous studies indicated ectoparasites that were associated with only a few bat species (Falcoz 1923, Séguy 1933, Aellen 1955, Anciaux de Faveaux 1976, Amr and Qumsiyeh 1993, 2016.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations